10.1016/S0271-7964(08)70484-1 (CrossRef Listing of Deleted DOIs, 2000)
Allergen immunotherapy (AIT) has been acknowledged as the only disease-modifying treatment for respiratory diseases since its introduction in 1911. Although the efficacy and safety have convincingly been established in numerous randomized clinical trials (RCTs), the AIT study results may vary substantially. Several factors that may influence the outcome of RCTs will be addressed. First, the choice of the primary endpoint is essential. Lack of validated endpoints with proven clinical relevance may contribute to the variation in study results. Secondly, heterogeneity of the patient population affects the study outcome, thereby raising the question of whether current selection criteria should be further optimized to capture those patients who will benefit from immunotherapy. Thirdly, variability and particularly low allergen exposure may lead to unsuccessful AIT trials. Fourthly, unsuccessful trials may stem from large placebo effects. Furthermore, discrepancies between Phase II and III studies are asking for cautious interpretation of Phase II studies when planning Phase III studies. Flaws in trial design, inadequate reporting of the clinical trial protocol and data may hamper the interpretation of study results. In addition, this review addresses specific aspects of AIT trial design in children and asthmatic patients. To improve future AIT trials, innovative solutions are urgently needed, including the establishment of an internationally accepted minimal clinically important difference (MCID), the validation of primary endpoints, the integration of field studies and allergen exposure chamber studies, and the publication of negative study results.